1995
DOI: 10.1161/01.hyp.26.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Mechanical Properties of Carotid Arteries From Normotensive and Hypertensive Rats

Abstract: Hypertension is known to decrease arterial distensibility and volumetric compliance, as reported from pressure-volume experiments and ring and strip studies of human and animal large arteries. However, recent data using noninvasive in vivo recording of vessel diameter suggest that the cross-sectional compliance of large arteries can be unchanged or even increased in hypertensive subjects. The present study was performed to test the hypothesis that differences between volumetric and cross-sectional compliance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…The identical values we observed for carotid wall elasticity and MS in the circumferential direction illustrates the anisotropy of the wall. 17,18 Thus our study demonstrates that the global mechanical behavior of the SHR CA is well adapted to the increase in circumferential wall stress. This finding is consistent with previous in vivo observations of an adaptation of arterial elasticity in genetic hypertension in rats and human beings.…”
Section: Cohuet Et Al Arterial Mechanical Strength In Shrsupporting
confidence: 54%
“…The identical values we observed for carotid wall elasticity and MS in the circumferential direction illustrates the anisotropy of the wall. 17,18 Thus our study demonstrates that the global mechanical behavior of the SHR CA is well adapted to the increase in circumferential wall stress. This finding is consistent with previous in vivo observations of an adaptation of arterial elasticity in genetic hypertension in rats and human beings.…”
Section: Cohuet Et Al Arterial Mechanical Strength In Shrsupporting
confidence: 54%
“…In this study, the investigated arterial segment showed a lengthening in systole, which is in concordance with previous results from video microscopy in rats [14] but contradictive to a previous study using sonomicrometry in a porcine model [15]. In the latter, a shortening of the carotid artery in systole was demonstrated.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, for measurement of carotid E inc , the classic assumption of equal stiffness in all directions may be highly questionable, a major point that we and others have previously and extensively discussed. 28,35,36 Taken together, these findings indicate that E inc should be considered to be only an "effective" measurement for clinical applications.…”
Section: Basic Concepts In Arterial Structure and Functionmentioning
confidence: 90%
“…31 However, these findings are limited to the circumferential direction (due to cross-sectional measurements) and might differ in the longitudinal axis. 35,36 Levels of compliance and distensibility differed in accordance with the topography of the vessels; for the radial artery, normal (operational conditions) or increased (isobaric conditions) values have been reported, whereas for the carotid artery, reduced (operational conditions) or normal (isobaric conditions) values were observed. 16,17,31,32,45 In middle-aged hypertensive patients, the mechanisms responsible for such minor changes in E inc remain difficult to elucidate, given that increased wall thickness might modify vascular stiffness.…”
Section: Carotid and Radial Arterial Wall Hypertrophy With Normal Walmentioning
confidence: 99%